2008
DOI: 10.1037/0022-0663.100.2.291
|View full text |Cite
|
Sign up to set email alerts
|

On warm conceptual change: The interplay of text, epistemological beliefs, and topic interest.

Abstract: The aim of this study was to go further than considering only cognitive factors to extend the understanding of the complex, dynamic underlying knowledge revision processes. Fifth graders were assigned to 2 reading conditions. Participants in 1 condition read a refutational text about light, whereas participants in the other read a traditional text. Within each reading condition, students had more or less advanced beliefs about scientific knowledge (complex and evolving vs. simple and certain), as well as high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(157 citation statements)
references
References 103 publications
10
136
2
8
Order By: Relevance
“…While several authors (Dole & Sinatra, 1998;Limón & Mason, 2002;Mason, Gava, & Boldrin, 2008;Pintrich, Marx, & Boyle, 1993;Sinatra & Pintrich, 2003) have shown that the affective and motivational characteristics of the learner, as well as various social, instructional and contextual factors, play a role in the adoption of conceptual change, our research was only focused on cognitive aspects of conceptual change (see Vosniadou, 2007 for a discussion).…”
Section: Introductionmentioning
confidence: 99%
“…While several authors (Dole & Sinatra, 1998;Limón & Mason, 2002;Mason, Gava, & Boldrin, 2008;Pintrich, Marx, & Boyle, 1993;Sinatra & Pintrich, 2003) have shown that the affective and motivational characteristics of the learner, as well as various social, instructional and contextual factors, play a role in the adoption of conceptual change, our research was only focused on cognitive aspects of conceptual change (see Vosniadou, 2007 for a discussion).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the use of texts has been identified as a powerful tool in the knowledge revision process (Sinatra & Broughton, 2011). One text type that has been shown to be successful at helping individuals revise misconceived knowledge is the refutation text (Alvermann & Hague, 1989;Alvermann & Hynd, 1989;Braasch, Goldman, & Wiley, 2013;Frède, 2008;Guzzetti, Snyder, Glass, & Gamas, 1993;Hynd, Alvermann, & Qian, 1997;Mason & Gava, 2007;Mason, Gava, & Boldrin, 2008;Tippett, 2010). Refutation texts explicitly acknowledge commonly held incorrect conceptions or beliefs about a topic, directly refute them, and provide a more satisfactory explanation (Hynd, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Refutational lessons have been shown to nurture long-term conceptual change across a wide range of grade levels (Cook, Bedford, & Mandia, 2014). Research has demonstrated that refutational texts can: 1) increase argumentative skills and raise awareness of the relevance of evidence to argument (Kuhn & Crowell, 2011); 2) foster critical thinking and encourage students to assess evidence and to draw valid conclusions (Berland &Reiser, 2011: Kuhn andCrowell, 2011); 3) provoke more interest compared to traditional textbooks (Manson, Gava, & Boldrin, 2008); and 4) resolve to some degree the issue that knowledge is often imparted as a set of unequivocal facts with a lack of argument in the classroom (Osborne, 2010).…”
Section: Climate Science Education and Scientific Argumentationmentioning
confidence: 99%